2020
DOI: 10.4269/ajtmh.19-0542
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of Depressive Symptoms and Associated Factors among Internal Migrants with Tuberculosis: A Cross-Sectional Study in China

Abstract: There are hundreds of millions of internal migrants in China, and tuberculosis (TB) is an important health threat to them. However, the mental health problems of internal migrants with TB in China have been ignored. The present study aimed to determine the prevalence of depressive symptoms and its associated risk factors among internal migrants with TB in China. A cross-sectional survey was conducted between June 2018 and March 2019 in Shenzhen, southern China. Data were collected from 1,057 internal migrants … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
7
0
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 27 publications
2
7
0
1
Order By: Relevance
“…In this study, we found that the prevalence of depressive symptoms was 52.94%, which is the same as 53.8% reported in a cross-sectional survey in Shenzhen, southern China [36], but much higher than that of the elderly in Korea (30.3%) and Mexico (29.1%) [37,38]. The heterogeneity of the prevalence among elderly people in different countries be because of differences of national culture and historical background as well as differences in survey samples of different assess scales and social support systems of the elderly in different countries.…”
Section: Prevalence Of Depressive Symptomssupporting
confidence: 86%
“…In this study, we found that the prevalence of depressive symptoms was 52.94%, which is the same as 53.8% reported in a cross-sectional survey in Shenzhen, southern China [36], but much higher than that of the elderly in Korea (30.3%) and Mexico (29.1%) [37,38]. The heterogeneity of the prevalence among elderly people in different countries be because of differences of national culture and historical background as well as differences in survey samples of different assess scales and social support systems of the elderly in different countries.…”
Section: Prevalence Of Depressive Symptomssupporting
confidence: 86%
“…Studies also focused on the social determinants of (mental) health; these are the conditions in which people are born, live, learn, work, play, and age, and have a significant influence on wellbeing [ 291 ]. Factors such as age, social or socioeconomic status, social support, financial strain and deprivation, food insecurity, education, employment status, living arrangements, marital status, race, childhood conflict and bullying, violent crime exposure, abuse, discrimination, (self)-stigma, ethnicity and migrant status, working conditions, adverse or significant life events, illiteracy or health literacy, environmental events, job strain, and the built environment have been linked to depression, among others [ 52 , 133 , 235 , 236 , 239 , 252 , 269 , 280 , 292 , 293 , 294 , 295 , 296 , 297 , 298 , 299 , 300 , 301 , 302 , 303 , 304 , 305 , 306 , 307 , 308 , 309 , 310 , 311 , 312 , 313 , 314 , 315 , 316 , 317 , 318 , 319 , 320 , 321 , 322 , 323 , 324 , 325 , 326 ,…”
Section: Resultsmentioning
confidence: 99%
“…Lack of social support was the most common source of social stress faced by TB patients [ 31 ]. Family function is an important source of social support for TB patients, and its effect on psychological distress has been reported [ 8 , 9 ]. Our study also found that patients with severe family dysfunction were 4 times more likely to experience psychological distress than patients with good family functioning.…”
Section: Discussionmentioning
confidence: 99%
“…Family function was divided into three levels, 0 to 3 on a scale of a severely dysfunctional family, 4 to 6 on a scale of a moderately dysfunctional family, and 7 to 10 on a scale of a highly functional family [ 34 ]. Family APGAR Questionnaire has been widely used in China and has good reliability and validity [ 8 ]. In this study, it has a high internal consistency (Cronbach’s α = 0.937).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation